If you only knew - Hernando, Jorgea; Danner, Paul M.; Kaegi, Jacqueline; Harkavy, Juliana; BV Productions (Firm); Leomark Studios (Firm) ([Miami Beach, FL] : BV Productions, 2011)
After being abused by her boyfriend in her youth, a stunning fashion designer develops Alzheimer's at an unusally early age. With her memory fast-fading, she reluctantly faces the demons of her past, while dreaming of a better future for her son. --
Originally released as a motion picture in 2011.
Juliana Harkavy, William Haze, Ford d'Aprix, Christie Prades, Kourtney Brown, Marc Durso, Haley Higgins, Nando del Castillo.
Cinematographer, Frank Martin ; editor, Jokes Yanes ; music, Marc Vee.
In English with English subtitles; with an additional Spanish dubbed version with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 6, 2016).
Keywords: Alzheimer's disease -- Drama; Family violence -- Drama; Fashion design -- Drama; Mothers and sons -- Drama; Feature films; Internet videos; Streaming video